Influence of mining-geological conditions and technogenic factors on blastholes stability during open mining of apatite-nepheline ores - M. N. Overchenko; S. A. Tolstunov; S. P. Mozer (Записки Горного института, 2018)
The paper presents the results of borehole stability research and considers possible causes of emergencies. The features of the blast hole drilling process are analyzed taking into account the properties of the rock. Based on the distribution of speed of drill fines removal from the well, an algorithm for selecting drilling modes is proposed. The nature of change in the size of the holess over time has been analyzed. This paper investigates the influence of rock fracturing and its water content on borehole stability.